On being the boss - McEwan, Barbara (Crisp Pub. Menlo ParkUS, 1995)
Provides specific strategies for fulfilling the expectations of upper management, while facilitating a peaceful, calm and empowering workplace environment. Addresses issues including: communication strategies in conflict resolution; ethical concepts including being a role model of responsible, personal, and professional behaviour; developing fair, reasonable rules and expectations for the workplace; earning respect; and avoiding power struggles with employees. Also analyses a number of situations that bring an individual employee's rights into conflict with the needs of the majority. N.B. : The framework used for management decisions is the United States Constitution.